Disparities in health-related quality of life between patients with primary and secondary antibody deficiencies - Andy Ka Chun Kan, MBBS (Hons), MRes; Valerie Chiang, MBBS; Elaine Y.L. Au, MBBS, FRCPA; Chak Sing Lau, MD (Hons), FRCP; Philip H. Li, MD, FRCP, FRCPath, FAAAAI (Journal of Allergy and Clinical Immunology: Global)
Background: The impact and burden of antibody deficiencies, especially secondary antibody deficiency (SAD), among adult patients remain largely understudied. Specifically, the health-related quality of life (HRQoL) of patients with SAD, compared to patients with primary antibody deficiency (PAD) remains unknown. Objective: Our aim was to characterize and compare the HRQoL of adult patients diagnosed with PAD and SAD. Methods: Clinical and HRQoL questionnaire survey data (from the SF-36v2 Health Survey [SF-36v2]) of all adult patients diagnosed with PAD or SAD at Queen Mary Hospital (the only adult immunology center in Hong Kong) were analyzed and compared to data on the general population. Results: Among the 33 adult patients with antibody deficiency, 22 (66.7%) and 11 (33.3%) had PAD and SAD, respectively. Compared to the general population, patients with PAD scored significantly lower in 3 of 8 domains of the SF-36v2, namely, Role-Physical (81.0 vs 90.4 [P = .020]), Bodily Pain (70.6 vs 84.0 [P = .013]), and Social Functioning (80.1 vs 91.2 [P = .024]). In comparison, patients with SAD scored significantly lower HRQoL in 5 of 8 domains of the SF-36v2, namely, Physical Functioning (64.1 vs 91.8 [P = .032]), Role-Physical (61.9 vs 90.4 [P = .018]), Bodily Pain (51.6 vs 84.0 [P = .003]), General Health (32.9 vs 56.0 [P = .006]), and Social Functioning (61.4 vs 91.2 [P = .027]), as well as in the Physical Component Summary (41.7 vs 53.0 [P = .004]). Upon direct comparison with patients with PAD, patients with SAD had significantly poorer HRQoL in the Physical Component Summary (41.7 vs 49.9 [P = .015]). Conclusion: Patients with SAD reported significantly poorer HRQoL than patients with PAD. Despite significantly greater impairment in HRQoL, patients with SAD often remain underrepresented and may warrant particular attention in terms of physical support and resource allocation.